Frequencyof Medical Conditions in Patients of Low Socioeconomic Status Seeking Dental Treatment - Maaz Asad; Kashif Ikram; Asaad Javaid Mirza; Marwah Berkathullah (Journal of Bahria University Medical and Dental College, 2015)
Objective:To determine the frequency of medical conditions prevalent in an area of inhabitants with low socioeconomic status seeking dental treatment Materials and Methods:A cross-sectional study was performed employing medical histories of 341 patients reporting for dental treatment from June 2011- December 2011 at Baqai Dental College Hospital (BDCH).A questionnaire was designed consisting of demographic data and various common systemic diseases. The doctors on duty in the Department of Oral Diagnosis and Radiology were briefed about filling out the questionnaire and requested to fill one for each patient coming to BDCH for dental treatment. The collected data was analyzed using Statistical Package for Social Sciences (SPSS) version 17. Results:The data was compiled keeping in view the most common prevailing disease in dental patients and relationship between gender and occurrence of systemic diseases.The results revealed that among the subjects of this study, the most prevailing medical problem was Hypertension 37(8.4%). Hepatitis 19(4.3%) and joint pains 16(3.60%) respectively were the 2nd and 3rd place common diseases.Regarding association between gender and occurrence of systemic diseases, hypertension (12.50%) and thyroid ailments (4.50%) were found to be more prevalent in females than males. Diabetes and hepatitis were more frequent in males while joint pain was found to be almost evenly distributed among both genders. Conclusion:The frequency of medical conditions prevalent in an area of inhabitants with low socioeconomic status seeking dental treatment was 8.2% hypertension, 4.3%hepatitis and 3.60% joint pains.